Human Resource Management Strategy in Higher Education for Functional Position Improvement - Sulistiyanto; Cristian Wiradendi; Budi Rianto; Arfah (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The development and promotion of academic staff are critical for enhancing institutional quality, faculty productivity, and career advancement in higher education. However, faculty members often face challenges in research productivity, administrative procedures, and institutional support that can hinder their academic promotion. This study aimed at examine the strategies for managing human resources for lecturers in tertiary education institutions in order to enhance the advancement of functional positions for lecturers. The research used mixed-methods approach design, combining both numerical and descriptive methods. The sample of this study consists of 30 permanent lecturers who work in universities in Indonesia. Questionnaire and interview data were analyzed descriptively and thematically to examine lecturers’ promotion challenges, human capital management strategies, and their impact on higher education quality. The research findings show that although lecturers understand the procedures for advancing functional positions, many still face barriers related to scientific publications and meeting credit points. Universities play a key role in providing the necessary support and facilitation to accelerate the advancement of functional positions. This research provides important perspectives on the significance of managing HR for lecturers in higher education to improve academic quality and foster lecturers’ careers.